Early feeding after colorectal surgery in children: Is it safe? - Arindam Ghosh; Somak Krishna Biswas; Kalyani Saha Basu; Sumitra Kumar Biswas (Wolters Kluwer Medknow Publications, 2020)
Aim of the Study: The aim of this study is to assess the role of early feeding after elective colorectal surgery in children and compare the outcome of feeding practice early versus traditional feeding. Study Design: A randomized controlled, single-center study was conducted over a period of 3 years (November 2015-October 2018) at a tertiary care center. Materials and Methods: Patients (n = 147), after colostomy closure (as elective colorectal surgery), were randomly selected for postoperative feeding initiation and were divided into two groups, namely the control (traditional feeding) group and study group (early feeding). In early group, feeding was initiated on the postoperative day 1 after the removal of nasogastric tube (removed after 16 h of surgery). Postoperative hospital stay and complications were compared among them. Statistical Analysis Used: Data were tabulated and analyzed in Microsoft Excel 2010. Results: Among 147 patients (boys[70] and girls [77]), the average age of colostomy closure was 4.36 years. Forty-five patients had early feeding and 102 traditional feeding. Average postoperative hospital stay was noted 5.62 ± 1.11 days for "Study group" and 8.1 ± 1.04 days for "Control group." Postoperative complications were found in 17 patients; 11 (7.5%) superficial surgical site infection (9 [8.8%] in control and 2 [4.4%] in study group) and 6 (4%) minor fecal fistulae (5 [4.9%] in control group and 1 [2.2%] in study group). None required any further surgical intervention. No mortality was reported. Conclusions: Early feeding initiation after elective colorectal surgery is safe, and postoperative hospital stay is significantly reduced. It is definitely a step forward in the era of fast track surgery in pediatric population.